Long-term mortality and causes of death among patients with mild traumatic brain injury: a 5-year multicenter study. (20th March 2020) - Sercy, Erica; Orlando, Alessandro; Carrick, Matthew; Lieser, Mark; Madayag, Robert; Vasquez, Donald; Tanner, Allen; Rubin, Benjamin; Bar-Or, David
ABSTRACT: Objective : Undergoing mild traumatic brain injury (mTBI) increases mortality risk, but it is unclear what drives this finding. This study explored associations with mortality in patients with mTBI. Methods : This was a retrospective study of patients with mTBI and controls admitted to six level 1 trauma centers in 1/1/2009-12/31/2013. Mortality data were from the CDC National Death Index. Patients with mTBI were identified by ICD-9 code, Glasgow Coma Scale 13–15, Injury Severity Score (ISS) <16, and loss of consciousness ≤1 hour. Controls had hospital length of stay ≤24 hours, ISS<16, and no head injury. Results : This study included 964 patients with mTBI and 5, 567 controls. mTBI was associated with a 47% increased 5-year mortality risk (HR = 1.47, 95% CL 1.08–2.01). Patients with mTBI were more likely to die of a neurodegenerative disease (17% vs 11%, P = .119). Cardiovascular (HR = 1.80, 95% CL 1.17–2.77), neurological (HR = 3.33, 95% CL 2.07–5.38), and respiratory (HR = 1.70, 95% CL 1.01–2.86) comorbidities were associated with mortality in patients with mTBI. Conclusions : Patients with mTBI are at increased mortality risk in the 5 years post-injury. Mortality in patients with mTBI was most influenced by preexisting conditions.